Continental mass change from GRACE over 2002-2011 and its impact on sea level - Baur, O.; Kuhn, Michael; Featherstone, Will (Springer - Verlag, 2013)
Present-day continental mass variation as observed by space gravimetry reveals secular mass decline and accumulation. Whereas the former contributes to sea-level rise, the latter results in sea-level fall. As such, consideration of mass accumulation (rather than focussing solely on mass loss) is important for reliable overall estimates of sea-level change. Using data from the Gravity Recovery And Climate Experiment satellite mission, we quantify mass-change trends in 19 continental areas that exhibit a dominant signal. The integrated mass change within these regions is representative of the variation over the whole land areas. During the integer 9-year period of May 2002 to April 2011, GIA-adjusted mass gain and mass loss in these areas contributed, on average, to −(0.7 ± 0.4) mm/year of sea-level fall and + (1.8 ± 0.2) mm/year of sea-level rise; the net effect was + (1.1 ± 0.6) mm/year. Ice melting over Greenland, Iceland, Svalbard, the Canadian Arctic archipelago, Antarctica, Alaska and Patagonia was responsible for + (1.4±0.2) mm/year of the total balance. Hence, land-water mass accumulation compensated about 20 % of the impact of ice-melt water influx to the oceans. In order to assess the impact of geocentre motion, we converted geocentre coordinates derived from satellite laser ranging (SLR) to degree-one geopotential coefficients. We found geocentre motion to introduce small biases to mass-change and sea-level change estimates; its overall effect is + (0.1 ± 0.1) mm/year. This value, however, should be taken with care owing to questionable reliability of secular trends in SLR-derived geocentre coordinates.